MECHANICAL STRENGTH OF FIBER VEGETABLE MERCERIZED OF SUGAR CANE AND BAMBOO - Outa, R.; Chavarette, F. R.; Louzada, M. J. Q. (Revista Brasileira de Engenharia de Biossistemas, 2016)
Currently the addition of synthetic and natural fibers has been applied in different areas, and due to environmental issues, some researchers have focused their studies for applications with natural fibers in the textile industry, construction, plastics and even automotive. This interest is further enhanced by reducing costs, hence the consumer selling prices. The motivation of this research is arising from previous studies of this author, whose crushed material from sugarcane bagasse was used to manufacture a composite binder originating from the sub-process of a sugar mill and alcohol. Thus, this research aims to analyze the mechanical strength characteristics of the traction and the elastic modulus of sugar cane and bamboo fibers, which, both transverselycut fibers fibrous line with about 150.0 mm, They were mercerized in a NaOH 10% solution. The final test results of mechanical tests of both fibers, show similar results to high impact materials and high materials and low density, with the proviso that the bamboo fiber has a higher tensile strength that the cane fiber , in which case, this difference is due to the structural feature amount of xylem and even the concentration of lignin in the region.